Iconographic analysis of pictorial type, as a nation builder in Argentina during the first half of the nineteenth century (1810 - 1852) - Palta Flaker, Deiner; Palta Flaker, Deiner; Palta Flaker, Deiner (Corporación Universitaria Americana, 2024)
This article analyzes representative examples of pictorial art in Argentina during the first half of the 19th century through the study of iconographic representations, which, when compared with written sources, reveal allegories, symbols and national identities. These show the socio-cultural transitions of political type, which were portrayed by foreign and native artists in the visual imaginary comprised by two periods 1810- 1829 and 1830 - 1852. In the first period, the beginnings of modern Argentine pictorial art express in their works the heroic legacy left by the liberation campaigns and the heroes of the country, within the framework of neoclassicism that will be reflected throughout the first half of the 19th century. In the second period the themes and symbols change to reflect a nationalism that gained strength through the image as a visual discourse by means of the dictatorial regime of General Juan Manuel de Rosas.